2009
DOI: 10.1007/s10615-009-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

There’s No Place Like Home: Preparing Children for Geographical and Relational Attachment Disruptions Following Parental Death to Cancer

Abstract: The death of a parent precipitates a number of profound losses and transitions for children, disrupting their sense of safety and security. Children who have lost both parents or who, due to divorce, are relocating across great distances following the death of their custodial parent incur a number of profound secondary losses, including place attachment disruptions. Work with this population should aim to create a holding environment for children to normalize and validate their experiences while keeping them o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 20 publications
1
28
0
2
Order By: Relevance
“…[1] Four studies in the review, as set out in Table 2, were scored as highly relevant for this study. [6,30,33,34] Werner-Lin et al found that, when children of divorced parents have a custodial critically ill parent, they experience loneliness, depression and worry about who will take care of them when their parents die. When their custodial parent dies, they experience multiple losses, such as loss of lifestyle, home, relatives and friends.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[1] Four studies in the review, as set out in Table 2, were scored as highly relevant for this study. [6,30,33,34] Werner-Lin et al found that, when children of divorced parents have a custodial critically ill parent, they experience loneliness, depression and worry about who will take care of them when their parents die. When their custodial parent dies, they experience multiple losses, such as loss of lifestyle, home, relatives and friends.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of the house symbolizes loss of attachment to the lost parent, and the transition to a new home and a new custodial adult or parent leaves the child with stress. [6] The child may blame the death and former divorce on the former non-custodial parent, and this may have an impact on the new bonding. They also found that a therapeutic relationship may help the child in the years after the custodial parent's death and through the transition process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations